A New Guanidine-Core Small-Molecule Compound as a Potential Antimicrobial Agent against Resistant Bacterial Strains - Noelia Morata-Moreno; Ramón Pérez-Tanoira; Almudena del Campo-Balguerias; Fernando Carrillo-Hermosilla; Marcos Hernando-Gozalo; Carlos Rescalvo-Casas; Ana V. Ocana; Pedro Segui; Carlos Alonso-Moreno; Francisco C. Pérez-Martínez; Milagros Molina-Alarcón (MDPI AG, 2024)
The guanidine core has been one of the most studied functional groups in medicinal chemistry, and guanylation reactions are powerful tools for synthesizing this kind of compound. In this study, a series of five guanidine-core small molecules were obtained through guanylation reactions. These compounds were then evaluated against three different strains of Escherichia coli, one collection strain from the American Type Culture Collection (ATCC) of E. coli ATCC 35218, and two clinical extended-spectrum beta-lactamase (ESBL)-producing E. coli isolates (ESBL1 and ESBL2). Moreover, three different strains of Pseudomonas aeruginosa were studied, one collection strain of P. aeruginosa ATCC 27853, and two clinical multidrug-resistant isolates (PA24 and PA35). Among Gram-positive strains, three different strains of Staphylococcus aureus, one collection strain of S. aureus ATCC 29213, and two clinical methicillin-resistant S. aureus (MRSA1 and MRSA2) were evaluated. Minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) experiments were reported, and the drop plate (DP) method was used to determine the number of viable suspended bacteria in a known beaker volume. The results from this assessment suggest that guanidine-core small molecules hold promise as therapeutic alternatives for treating infections caused by clinical Gram-negative and Gram-positive bacteria, highlighting the need for further studies to explore their potential. The results from this assessment suggest that the chemical structure of CAPP4 might serve as the basis for designing more active guanidine-based antimicrobial compounds, highlighting the need for further studies to explore their potential.